N-terminal lid swapping contributes to the substrate specificity and activity of thermophilic lipase TrLipE - Fang, Yakun; Liu, Fan; Shi, Yi; Yang, Ting; Xin, Yu; Gu, Zhenghua; Shi, Guiyang; Zhang, Liang (Frontiers in Microbiology, 2023)
TrLipE is a thermophilic lipase that has potential commercial applications because of its catalytic ability under extreme conditions. Consistent with most lipases, the lid of TrLipE is located over the catalytic pocket, controls the substrate channel to the active center, and regulates the substrate specificity, activity, and stability of the enzyme through conformational changes. TrLipE from Thermomicrobium roseum has potential industrial applications, which is hindered by its weak enzymatic activity. Here, 18 chimeras (TrL1-TrL18) were reconstructed by N-terminal lid swapping between TrLipE and structurally similar enzymes. The results showed that the chimeras had a similar pH range and optimum pH as wild TrLipE but a narrower temperature range of 40-80 °C, and TrL17 and the other chimeras showed lower optimum temperatures of 70 °C and 60 °C, respectively. In addition, the half-lives of the chimeras were lower than those of TrLipE under optimum temperature conditions. Molecular dynamics simulations indicated that chimeras had high RMSD, RMSF, and Bfactor values. When p-nitrophenol esters with different chains were used as substrates, compared with TrLipE, most of the chimeras had a low Km and high kcat value. The chimeras TrL2, TrL3, TrL17, and TrL18 could specifically catalyze the substrate 4-nitrophenyl benzoate, with TrL17 showing the highest kcat/Km value of 363.88 ± 15.83 L• min -1 • mmol -1 . Mutants were then designed by investigating the binding free energies of TrL17 and 4-nitrophenyl benzoate. The results indicated that single, double, and triple substitution variants (M89W and I206N; E33W/I206M and M89W/I206M; and M89W/I206M/L21I and M89W/I206N/L21I, respectively) presented approximately 2-to 3-fold faster catalysis of 4-nitrophenyl benzoate than the wild TrL17. Our observations will facilitate the development of the properties and industrial applications of TrLipE.